2020
DOI: 10.1016/j.ajhg.2020.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Consequences of the Transatlantic Slave Trade in the Americas

Abstract: According to historical records of transatlantic slavery, traders forcibly deported an estimated 12.5 million people from ports along the Atlantic coastline of Africa between the 16th and 19th centuries, with global impacts reaching to the present day, more than a century and a half after slavery’s abolition. Such records have fueled a broad understanding of the forced migration from Africa to the Americas yet remain underexplored in concert with genetic data. Here, we analyzed genotype array data from 50,281 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
124
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(149 citation statements)
references
References 67 publications
23
124
2
Order By: Relevance
“…Within Africans, red indicates a West African (aka African Rice Coast) ancestry (highest in the Mandenka of Senegal and Sierra Leone ethnic groups), orange a Central and South African ancestry (highest in the San of Namibia and Mbuti of Democratic Republic of the Congo), yellow an East African ancestry (highest in Maasai and Luhya of Kenya), and green a West-Central African ancestry (aka Bight of Benin) ancestry (highest in the Yoruba of Nigeria) analyses showed that, despite the highly variable levels of European and West African ancestry in all African American groups, the Gullah had a lower average level of European admixture than JHS African Americans (Figure 2). The lower European contribution in the Gullah corroborates known differences in ancestry proportions among African Americans in different U.S. states (Baharian et al, 2016;Bryc et al, 2015;Dai et al, 2020;Mathias et al, 2016;Micheletti et al, 2020;Patin et al, 2017), and confirms that subtle differences in African American population structure can exist at finer regional levels.…”
Section: African Ancestry Estimates Of Gullah African Americanssupporting
confidence: 71%
“…Within Africans, red indicates a West African (aka African Rice Coast) ancestry (highest in the Mandenka of Senegal and Sierra Leone ethnic groups), orange a Central and South African ancestry (highest in the San of Namibia and Mbuti of Democratic Republic of the Congo), yellow an East African ancestry (highest in Maasai and Luhya of Kenya), and green a West-Central African ancestry (aka Bight of Benin) ancestry (highest in the Yoruba of Nigeria) analyses showed that, despite the highly variable levels of European and West African ancestry in all African American groups, the Gullah had a lower average level of European admixture than JHS African Americans (Figure 2). The lower European contribution in the Gullah corroborates known differences in ancestry proportions among African Americans in different U.S. states (Baharian et al, 2016;Bryc et al, 2015;Dai et al, 2020;Mathias et al, 2016;Micheletti et al, 2020;Patin et al, 2017), and confirms that subtle differences in African American population structure can exist at finer regional levels.…”
Section: African Ancestry Estimates Of Gullah African Americanssupporting
confidence: 71%
“…Demographic forces such as population bottlenecks, expansions, and migration as well as adaptation to novel environments resulted in observable differences in continental patterns of genetic variation ( Nelson et al, 2008 ; Abecasis et al, 2012 ; Auton et al, 2015 ). These differing patterns were shaped by many historical events of migration which included the founding of the Americas by Amerindigenous populations, the colonization by Europeans, and the African slave trade ( Gravel et al, 2013 ; Homburger et al, 2015 ; Moreno-Estrada et al, 2014 ; Moreno-Estrada et al, 2013 ; Reich et al, 2012 ; Bryc et al, 2015 ; Conomos et al, 2016 ; Han et al, 2017 ; Baharian et al, 2016 ; Jordan et al, 2019 ; Micheletti et al, 2020 ). However additional complexities surrounding these events remain highly understudied.…”
Section: Introductionmentioning
confidence: 99%
“…(Egan, Knutson, Pereira, & von Schantz, 2017; Whitesell, Obi, Tamanna, & Sumner, 2018). However, significant differences in genetic (including admixture), environmental and socio-economic circumstances (Micheletti et al, 2020), precludes extrapolating those findings to the situation of Africans living in Africa. Sub-Saharan Africa, and particularly South Africa, is experiencing a profound health transition, characterized by the emergence of non-communicable diseases (NCDs) and the ageing of the population in both rural and urban areas (Mayosi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%